VD_FINDINFO HC / 2014 / 670 vom 1. Juli 2014 - VD Tribunal cantonal (2014)
RECONNAISSANCE DE LA DÉCISION, SÛRETÉS, RÉSERVE DE L'ORDRE PUBLIC | 335 al. 3 CPC (CH), 59 al. 2 let. b CPC (CH), 99 al. 3 let. c CPC (CH)